Un Tópico Innovado en Software: Ingeniería de Software Libre - Callejas Cuervo, Mauro (Ingeniería, 2004)
The purpose of this work is to consider a process to generate free software with a high Quality, through Kernel work, which are discriminated throughout the different levels of the software development cycle life. Also, this work shows the functions and main devices, which should be used to apply this innovative paradigm (free software engineering). Additionally, it shows some types of free software used in the computing world, in order to understand the importance of this revolutionary trend. Finally, this work illustrates briefly a practical case with some principles of this paradigm developed at the Arquidiócesis of Tunja.